Analysis of osteoblast, osteoclast levels and radiographic patterns in the healing process of bone fractures (preliminary research) - Norlaila Sarifah; Lusi Epsilawati; Azhari Azhari; Mieke Hermiawati Satari; Bambang Pontjo Priosoeryanto; Isnur Hatta; Annisa Fitriyana (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2021)
Objectives: The healing process of a bone fracture goes through many phases. The hard callus phase was critical where the original structure was conducted. The hard callus growth depends on osteoblasts and osteoclasts active, and this condition can be analyzed on the radiograph. This study aimed to examine the analysis of bone fracture healing between osteoblasts and osteoclast numbers and radiographic patterns. Materials and Methods: The study used 12 male Wistar rats with an incomplete fracture in the right femur made by a dental tapered bur with 0.3 mm in length and 0.2 mm in depth. Digital radiographic examinations were carried out on days 0, 5, 10, 17, and 25 after fracturing in a lateral position. Furthermore, a radiographic analysis was performed using Image-J to obtain changes in the value of length and depth in the healing area. The research was conducted to find the radiopaque and radiolucent patterns and the number of osteoblasts and osteoclasts. Results: This study resulted in a change in the radiograph pattern. Callus formation resulted in fracture areas with a smaller distance from day 0 to day 25. The bone healing process begins with granulation tissue formation, followed by the gradual replacement of the connective tissue and bone. This process is comparable to the increase in osteoblasts up to day 25, which blocks bone resorption. Osteoclasts regulate bone resorption, and their number increases after 10 and 17 days to replace bone formation. Osteoclasts decline after 25 days because osteoblasts inhibit them, which control bone formation. Conclusion: The conclusions were obtained there are changes in the radiograph pattern. The radiopaque increased while the radiolucent decreased; the osteoclast pattern tended to be stable and lowered while the osteoblasts increased during the fracture healing process. The correlation of all the factors is very closely related.